2020
DOI: 10.1016/j.annemergmed.2020.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Injury Patterns Associated With Physical Elder Abuse: Analysis of Legally Adjudicated Cases

Abstract: Study objective: Elder abuse is common and has serious health consequences but is underrecognized by health care providers. An important reason for this is difficulty in distinguishing between elder abuse and unintentional trauma. Our goal was to identify injury patterns associated with physical elder abuse in comparison with those of patients presenting to the emergency department (ED) with unintentional falls.Methods: We partnered with a large, urban district attorney's office and examined medical, police, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
0
21
0
6
Order By: Relevance
“…The design of the included studies concerned eight descriptive studies [13,[21][22][23][24][25][26][27], three case studies [28][29][30], five narrative reviews [11,[31][32][33][34], six mixed methods studies [12,[35][36][37][38][39] and two books [40,41]. See Tables 1, 2, 3 and 4 for characteristics studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design of the included studies concerned eight descriptive studies [13,[21][22][23][24][25][26][27], three case studies [28][29][30], five narrative reviews [11,[31][32][33][34], six mixed methods studies [12,[35][36][37][38][39] and two books [40,41]. See Tables 1, 2, 3 and 4 for characteristics studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the descriptive studies (n = 8) showed moderate to good quality [13,21,24,26,27]. Most of the mixed methods studies (n = 6) showed low quality [12,[35][36][37].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Annals, Rosen et al 21 present the results of a carefully conducted study to identify physical patterns associated with elder abuse. The authors examined the records of successfully prosecuted cases and compared the patterns of physical injury in those cases with those of older adults who presented to the ED after an unintentional fall.…”
mentioning
confidence: 99%